IMPLEMENTASI PEMBELAJARAN PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM KURIKULUM PENDIDIKAN DASAR - Idham, Nurfadhila; Syukur, Muhammad (Social Landscape Journal, 2024)
This research was conducted to find out; 1) Implementation of the Learning Project for Strengthening the Profile of Pancasila Students at SD Inpres Bonto-Bontoa, 2) Supporting and inhibiting factors in the Implementation of Learning for the Project for Strengthening the Profile of Pancasila Students at SD Inpres Bonto-Bontoa, 3) Attitudes of student diversity in implementing the Project for Strengthening the Profile of Pancasila Students in SD Bonto-Bontoa Inpres Elementary School. This type of research is qualitative research using a case study approach. The number of informants in this research was 6 teachers who were determined through Purposive Sampling, with the teacher criteria being: 1) Teachers who currently teach at SD Inpres Bonto-Bontoa and 2) Teachers who have implemented the learning of the Pancasila Student Profile Strengthening Project. Data collection techniques are observation, interviews and documentation. Data validity is checked by member check. Data analysis, namely data condensation, data presentation and conclusion drawing.